SKRINING ANEMIA DAN PEMBERIAN SUPLEMENTASI FE PADA IBU HAMIL DAN WANITA USIA SUBUR (WUS) SEBAGAI UPAYA PENCEGAHAN ANEMIA KEHAMILAN - Erwin Kurniasih; Rini Komalawati (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2020)
Background: One of the causes of high maternal and infant mortality rates (IMR) is anemia of pregnancy and chronic energy deficiency (KEK). Anemia and KEK in pregnant women can increase the risk of low birth weight babies (LBW), premature birth, maternal and infant mortality and stunting (short children).To prevent this from happening, it is necessary to carry out screening and Fe supplementation as a preventive measure to prevent anemia in pregnancy. Activity This community service aims to screen for anemia and KEK pregnant women and women of childbearing age (WUS) as well as the provision of Fe supplementation for prevent iron deficiency anemia. Method: The method used is involving community as a form of empowerment such as measuring LiLA and levels of hemoglobin (Hb), BMI, and distribution of Fe supplementation. Besides that, it is also done education about anemia in pregnancy. The population in this activity is women aged fertile 15-40 years, a total of 42 people in Sambirobyong Hamlet, Pangkur Village,Ngawi Regency. Results: The results show that from 42 women of childbearing age in the hamlet Sambirobyong were screened, there were 3 people (7%) women of childbearing age temporary anemia 1 person (2%) with anemia status plus KEK. From 4 WUS people for age <20 years as many as 2 people (50%) with 1 person condition pregnant with anemia and 1 non-pregnant with anemia. While 2 people(50%) aged >35 years with 1 pregnant condition with anemia + KEK and 1 non-pregnant people with anemia. There is 1 person (2%) experiencing the risk of SEZ. Conclusion: Screening results show that anemia and KEK are more common WUS group aged <20 years and >35 years. It is necessary to carry out periodic evaluations every months and giving Fe supplementation to WUS who are still anemic and the risk of KEK and education on the importance of quality nutrition to prevent these complications.